2018
DOI: 10.1007/s12223-018-0603-6
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of resistance genes in Listeria monocytogenes isolates and their presence in the extracellular DNA of biofilms: a case study from the Czech Republic

Abstract: The alarming occurrence of antibiotic resistance genes in food production demands continuous monitoring worldwide. One reservoir of resistance genes is thought to be eDNA. There is currently little available information in Europe about either the extracellular DNA distribution of the bacterium or the spread of resistance genes in L. monocytogenes. Therefore, our aims were to give insight into the Listeria monocytogenes resistance situation in the Czech Republic and assess the presence of resistance genes in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 47 publications
1
1
0
Order By: Relevance
“…monocytogenes are multi-resistant for five or six antibiotics in this study but also showed susceptibility to gentamicin, erythromycin, tetracycline, vancomycin, trimethoprimsulfamethoxazole, ciprofloxacin, and chloramphenicol which are considered as secondchoice therapy in the treatment of listeriosis when there is resistance to β-lactamic or patients allergic to them [39]. Other investigators have also reported similar observations [19,20,33,42] that demonstrated the susceptibility to many antimicrobials such as sulfamethoxazole-trimethoprim, erythromycin, vancomycin, tetracycline, ciprofloxacin, chloramphenicol in L. monocytogenes strains recovered from humans, foods, and others.…”
Section: Discussionsupporting
confidence: 79%
“…monocytogenes are multi-resistant for five or six antibiotics in this study but also showed susceptibility to gentamicin, erythromycin, tetracycline, vancomycin, trimethoprimsulfamethoxazole, ciprofloxacin, and chloramphenicol which are considered as secondchoice therapy in the treatment of listeriosis when there is resistance to β-lactamic or patients allergic to them [39]. Other investigators have also reported similar observations [19,20,33,42] that demonstrated the susceptibility to many antimicrobials such as sulfamethoxazole-trimethoprim, erythromycin, vancomycin, tetracycline, ciprofloxacin, chloramphenicol in L. monocytogenes strains recovered from humans, foods, and others.…”
Section: Discussionsupporting
confidence: 79%
“…Studies comparing the profiles of selected genes of eDNA and genomic DNA (gDNA) revealed substantial similarities in the primary sequence of both nucleic acids, but also confirmed significant differences [9,15‐17]. Although eDNA is widespread in the environment (soil, sediments, oceans, and freshwater), little is known about the origin of biofilm eDNA.…”
Section: Introductionmentioning
confidence: 99%